Impact of Bioethanol and VCO Oil Additives on Power Output and Exhaust Gas Emissions in a 2-Stroke Gasoline Engine - Hariyanto, Rudi; Septiningsih, Dwi; Widiharsa, F.A; Ma'ruf, Mochamad (TRANSMISI, 2025)
This research focuses on evaluating the impact of adding Virgin Coconut Oil (VCO) and bioethanol on the power output and exhaust gas emissions of a 2-stroke motorcycle engine. In 2-stroke engines, lubricating oil is crucial for mixing with the fuel and lubricating the cylinder walls to reduce friction and wear. This study aims to investigate how varying concentrations of VCO oil and bioethanol affect engine performance and emissions. VCO oil primarily contains saturated fatty acids, including about 53% lauric acid and 7% caprylic acid. The study utilized bioethanol derived from sugar cane molasses to enhance the burning point of VCO oil. Exhaust emissions are the by-products of fuel combustion released through the engine’s exhaust system. Engine performance refers to its ability to convert fuel into useful power. The results indicate that the power output with 500 ml of ethanol mixed with VCO oil outperforms other mixtures, including pure VCO and lower ethanol concentrations. Additionally, higher ethanol concentrations in VCO oil lead to improved combustion efficiency and reduced exhaust gas emissions. This study demonstrates that optimizing ethanol and VCO oil ratios can enhance engine performance and reduce emissions.